Pertanggungjawaban Notaris dalam Pembuatan Akta Nominee: Analisis Putusan PN Gianyar No. 259/Pdt.G/2020 - Elva Melvina Oktasari; Umar Hasan; Syamsir Syamsir (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Nominee agreements, also known as name-lending agreements, are sometimes used as a means of legal circumvention. They are misused by providing opportunities for foreigners to evade the law and acquire land in Indonesia. This study aims to examine the legal position of nominee agreements from the perspective of contract law and national agrarian law, as well as to compare them with regulations in several other countries. The normative legal research method was used in this investigation. The results show that nominee agreements are legally invalid because they violate the provisions of the Basic Agrarian Law and do not meet the requirements for a valid agreement, especially in relation to the element of valid causa. Therefore, strict regulations are needed to ensure legal certainty and protect national agrarian sovereignty.